The Influence of Peat Water on the Physical Properties of Underwater Concrete - Mizam, Ibnu Munawar; Ismeddiyanto; Kurniawandy, Alex (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2024)
Casting concrete underwater is concrete used for structural work underwater. The main problem in underwater casting is the separation of concrete constituent materials. Casting underwater also does not involve compaction. This study will examine the effect of peat water on the physical properties of underwater cast concrete. The additive used in this study is in liquid form, with a mixture of anti-washout material 1.8% and self-compacting concrete 5% to the weight of cement. The obtained slump flow value is 470 mm. The results of volume weight testing on variations of clean water mixtures immersed in clean water for seven days are 2248,14 kg/m3 and 2258,96 kg/m3 for 28 days, variations of clean water mixtures immersed in peat water for seven days are 2224,49 kg/m3 and 2219,39 kg/m3 for 28 days, and variations of peat water mixtures immersed in peat water for seven days are 2202,50 kg/m3 and 2191,08 kg/m3 for 28 days. The decrease in volume weight occurs in variations immersed in peat water. The results of porosity testing on 7-day and 28-day concrete age variations of peat water mixtures immersed in peat water are 9,94% and 10,78%, variations of clean water mixtures immersed in peat water are 9,84% and 10,28%, and variations of clean water mixtures immersed in clean water are 9,73% and 8,70%. The SEM test results show the surface shape of concrete using a magnification of 1000x, more pores on variations of peat water mixtures immersed in peat water, and variations of clean water mixtures immersed in peat water have uneven surfaces and pores. In contrast, variations of clean water mixtures immersed in clean water have better surfaces. The additive used can work well with peat water and clean water.